Forgotten trials of the Holocaust - Bazyler, Michael J.; Tuerkheimer, Frank M. (New York : New York University Press, 2014)
"In the wake of the Second World War, how were the Allies to respond to the enormous crime of the Holocaust? Even in an ideal world, it would have been impossible to bring all the perpetrators to trial. Nevertheless, an attempt was made to prosecute some. Most people have heard of the Nuremberg trial and the Eichmann trial, though they probably have not heard of the Kharkov Trial--the first trial of Germans for Nazi-era crimes--or even the Dachau Trials, in which war criminals were prosecuted by the American military personnel on the former concentration camp grounds. This book uncovers ten "forgotten trials" of the Holocaust, selected from the many Nazi trials that have taken place over the course of the last seven decades. It showcases how perpetrators of the Holocaust were dealt with in courtrooms around the world--in the former Soviet Union, the United Kingdom, Israel, France, Poland, the United States and Germany--revealing how different legal systems responded to the horrors of the Holocaust. The book provides a graphic picture of the genocidal campaign against the Jews through eyewitness testimony and incriminating documents and traces how the public memory of the Holocaust was formed over time. The volume covers a variety of trials--of high-ranking statesmen and minor foot soldiers, of male and female concentration camps guards and even trials in Israel of Jewish Kapos--to provide the first global picture of the laborious efforts to bring perpetrators of the Holocaust to justice. As law professors and litigators, the authors provide distinct insights into these trials."--
The Kharkov Trial of 1943: The First Trial of the Holocaust? -- The Trial of Pierre Laval: Criminal Collaborator of Patriot? -- The Dachau Trial under U.S. Army Jurisdiction -- The Trial of Amon Gö̈th in Postwar Poland: Poland's "Nuremberg" -- The Hamburg Ravensbrück Trials in British-Occupied Germany: Women as Perpetrators, Women as Victims -- The Einsatzgruppen Trial at Nuremberg: Did Anyone have to follow Orders to Kill? -- The Jewish Kapo Trials in Israel: Is there a Place for the Law in the Gray Zone? -- The Frankfurt Auschwitz Trial: The Germans Trying Germans under German Law -- The Trial of Feodor Fedorenko: Treblinka Relived in a Florida Courtroom -- The Trial of Anthony Sawoniuk at the Old Bailey: The Holocaust in the British Courtroom.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: War crime trials -- History -- 20th century; War crime trials -- Europe -- History -- 20th century; Holocaust, Jewish (1939-1945); War criminals -- Europe -- Trials, litigation, etc; Holocauste, 1939-1945.; Procès (Crimes de guerre) -- Europe -- Histoire -- 20e siècle.; Procès (Crimes de guerre) -- Histoire -- 20e siècle.; HISTORY -- Holocaust; LAW -- Criminal Law -- General; HISTORY -- Jewish; LAW -- International; War crime trials; War criminals; Europe; Judenvernichtung; Nationalsozialistischer Verbrecher; Kriegsverbrecherprozess; 1900-1999; History; Trials, litigation, etc